IMPLEMENTATION OF THE DEATH PENALTY IN NARCOTIC CRIMINAL CASES (CASE STUDY OF DECISION NUMBER 203/PID.SUS/2019/PN.BLS.) - Kartika, Tantri; Affila (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The problem of abuse and illicit trafficking of Narcotics in Indonesia is still exacerbated by the process of Law Enforcement, Eradication of distribution and circulation illegal narcotics in this country. Law Number 35 of 2009 concerning Narcotics has clearly and clearly stated that perpetrators of illicit trafficking of Narcotics (narcotics syndicates) are subject to death penalty. Death penalty is one of the oldest types of punishment, as old as mankind. Death penalty is also the most interesting form of punishment studied by experts because it has a high value of contradiction or conflict between those who agree with those who disagree. In the decision being reviewed, namely decision number 203/Pid.Sus/2019/PN.Bls, that by taking into account, Article 114 paragraph (2) Jo. Article 132 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics and Law Number 8 of 1981 concerning Criminal Procedure Code and other relevant laws and regulations, the Panel of Judges sentenced the Defendant Suci Ramadianto Als Suci Als Iir Bin Subandi with death penalty.